A probiotic and mixed-enzymes combination reduces the inflammatory response, faecal shedding and systemic spread of Campylobacter jejuni in broilers - K. Gibbs; L. Lacharme-Lora; Y. Dersjant-Li; C. Evans; P. Wigley (Journal of Applied Animal Nutrition)
Recent research has questioned the notion that Campylobacter jejuni is a harmless resident of the avian gastrointestinal tract (GIT). The following trial examined the effect of dietary supplementation with a mixture of enzymes and Bacillus-based probiotics on growth performance, C. jejuni colonisation, GIT immune responses, faecal shedding and extra-intestinal spread in broilers. Fifty-eight, Ross 308 d-old broilers were randomly assigned to one of four treatments, giving 14 or 15 birds/pen. Birds were given nutritionally complete, complex, phased diets unsupplemented (two treatments) or supplemented (two treatments) with a multi-enzyme containing 2,000 U/kg xylanase, 200 U/kg amylase and 4,000 U/kg protease, and 75,000 cfu/g of a combination of three strains of Bacillus amyloliquefaciens. One control and one supplemented diet group contained birds orally challenged with 105 cfu C. jejuni strain M1 on d 21 of age. Among challenged birds, the mixed-enzymes and probiotic combination numerically reduced faecal C. jejuni shedding (-98% vs challenged control) three days-post-infection (d.p.i.), and at 7 d.p.i. numerically reduced C. jejuni colonisation of the ileal mucosa (-1000-fold vs control) and totally inhibited systemic spread of C. jejuni to the liver, compared to the control (P<0.05). It suppressed early pro-inflammatory chemokine response seen in the ileum, caecum and caecal tonsil tissues (at 3 d.p.i.) in challenged control birds (-18 to -46-fold; P<0.05) and altered expression of pro-inflammatory (IL-1β, IL-6, IL-17A and IL-17F) and regulatory (IL-10 and TGF-β) cytokines. The data demonstrated inhibition of a sustained pro-inflammatory response to C. jejuni infection and improved intestinal barrier integrity in supplemented birds. This highlighted the importance of looking beyond simple measurements of feed conversion and body weight gain when seeking to understand the effects and mode of action of poultry dietary interventions. Achieving a favourable balance between the gut, immune function, microbiome and nutrition should be the goal for achieving good gastrointestinal health and optimal performance.